Peningkatan Kemampuan Membaca Pemahaman Melalui Penerapan Metode Survey, Question, Read, Recite, and Review (SQ3R) pada Siswa Kelas III di SDN. No. 054/XI Muara Air Tahun 2016/2017 - Yusmaidar Yusmaidar (Universitas Batanghari Jambi, 2019)
This study aims to improve the reading comprehension ability of grade III students at SDN. No. 054/XI Muara Air year 2016/2017 Through the Application of Survey, Question, Read, Recite, and Review (SQ3R) Methods. The research conducted is classroom action research. The study was conducted at SDN. No. 054/XI Muara Air, Kumun Debai District, Sungai Penuh City, Jambi Province. This study involved five third grade students. Classroom action research was conducted in two cycles, each cycle consisting of four activities, namely planning, implementation, observation, and reflection. The research data was collected through tests and processed using simple statistical tests. The results showed that the application of the SQ3R method can improve student learning activities. All students have been able to read reading material quickly and thoroughly, make questions based on the contents of the reading, write answers to questions that have been made, and dare to read the results in front of the class. In addition, students also have the courage to respond well to answering teacher questions and providing responses to the results of training from other students. The application of the SQ3R method can also improve student learning outcomes. The average value of students increased from 56.00 (pre-action) to 68.00 in Cycle I and 78.00 in Cycle II. In addition, student learning completeness also increased from 40.00% (pre-action) to 80.00% in Cycle I and 100.00% in Cycle II. Thus, the application of the SQ3R method can improve the reading comprehension ability of third grade students at SDN. No. 054/XI Muara Air year 2016/2017